Importing, Productivity and Absorptive Capacity in Sub-Saharan African Manufacturing Firms - Neil Foster-McGregor; Anders Isaksson; Florian Kaulich (The Vienna Institute for International Economic Studies (wiiw), 2013)
Our study extends the recent literature on the importer-productivity relationship to a firm-level dataset for sub-Saharan Africa. Using a cross-section sample of 3090 firms in 19 countries, we find that importers are more productive than non-importers. The observed importer premium is found to be robust to firm-specific characteristics and to a number of alternative estimation methods. Furthermore, we examine the importance of absorptive capacity in enhancing the benefits from importing. Using recently developed quantile threshold regression methods, we find that higher levels of absorptive capacity, as measured by human capital, are associated with a stronger relationship between importing and productivity.
Keywords: D24; F10; M20; L10; 330; importing; productivity; sub-Saharan Africa; absorptive capacity; human capital